A Review on the Anti-Inflammatory Activity of Nyctanthes Arbor Tristis (Parijata) - K. Divya Bharathi; A. Sathvika; K. Krishnaveni; B. Aparna; K. Laxmi Manasa (International Journal of Pharmacy and Analytical Research, 2026)
Nyctanthes arbor tristis, commonly known as the night-flowering jasmine. Nyctanthes arbor tristis has been traditionally used for its various therapeutic properties, including anti- inflammatory, analgesic, anti-pyretic, anti-microbial, and hepatoprotective effects. Various parts of the plant are used medicinally to cure various diseases since centuries ago. It is a rich source of important phytochemicals like nycanthine, astringent principle, beta cortisol, coloring matter, tannins, flavonoids, cardiac glycosides, saponins and alkaloids etc. Pharmacological actions of Harsinghar include cholagogue, anthelmintic, laxative, antipyretic, diaphoretic, diuretic; for which the the plant is employed in the treatment of skin disorders, dandruff, malaria, different types of fever, hemorrhoids, palpitation, cough, excessive menstrual bleeding menstrual etc. Medical importance Help relieve fever, cough, and cold Reduce inflammation and pain Support digestive health